KREATIVITAS SENI MEMBATIK MENGGUNAKAN MOTIF BAWA PADA JURUSAN KRIYA KREATIF BATIK DAN TEKSTIL DI SMKN 3 KOTA BIMA - Rahmawati, Titin; Roslyn, Roslyn (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2023)
Indonesia is a nation rich in cultural and artistic treasures, consisting of several islands, tribes that are very famous around the world by having a diversity of culture and artistic creativity, namely traditional clothes and fabrics typical of their respective regions, one of which is batik. The type of research that will be used is a type of research that is qualitative descriptive "This research aims to find out the process of creativity of the art of batik using the motif of bringing in students of class XII of the Department of Textiles Smkn 3 Bima and knowing the quality of the results of the work.  The results of research on student batik works are relatively very good, from their own motives using local motifs that can attract the attention of the local community, because onions are the largest income of milky milk farmers. And the discussion about the process of student creativity using bawa motifs combined with uma lengge motifs or bima traditional houses in one cloth with batik writing techniques. The conclusion that the process of working on the art of batik using the motive of carrying out is to carry out learning activities, where students are required to have creative ideas and follow the stages that support the success of the work. The advice is for a new generation of batik makers, presumably make batik works as a reference and have creative ideas, cultural insights and traditions in batik work.